2017
DOI: 10.2527/tas2017.0032
|View full text |Cite
|
Sign up to set email alerts
|

Dietary forage to concentrate ratio and sunflower oil supplement alter rumen fermentation, ruminal methane emissions, and nutrient utilization in lactating cows1

Abstract: The effects of supplementing high- or low-concentrate diets with sunflower oil (SO) on rumen fermentation, nutrient utilization, and ruminal methane (CH4) emissions in lactating cows were examined. Four multiparous Nordic Red dairy cows fitted with rumen cannulae were used in a 4 × 4 Latin square with a 2 × 2 factorial arrangement of treatments and 35-d periods. Experimental treatments comprised iso-nitrogenous total mixed rations based on grass silage with forage to concentrate ratio of 65:35 or 35:65 supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
23
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 31 publications
14
23
2
2
Order By: Relevance
“…The decrease in NDF digestibility could be related to increased content of soluble nutrients as the forage:concentrate ratio decreased, which could reduce rumen pH and increase digesta passage rate, reducing fiber digestibility. Similar results were obtained by Ma et al (2014) and Bayat et al (2017) in sheep and cow, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in NDF digestibility could be related to increased content of soluble nutrients as the forage:concentrate ratio decreased, which could reduce rumen pH and increase digesta passage rate, reducing fiber digestibility. Similar results were obtained by Ma et al (2014) and Bayat et al (2017) in sheep and cow, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Chung et al (2011) reported that when Holstein cows were fed a diet based on whole-crop barley silage supplemented with 150 g/kg of DM of a high-fat linseed, MY was reduced by 33%, but there was no effect on MY when a high-fat linseed supplement was fed with a diet based on chopped grass hay. Similar results have been reported from an experiment by Bayat et al (2017), where sunflower oil fed at a rate of 50 g/kg DM to Nordic red dairy cows was more effective in reducing MY when concentrate constituted a low (35% of DM) proportion of the basal diet than when concentrate constituted a high (65% of DM) proportion. Our results indicate that the type of grain in the basal diet of dairy cows does not affect the methane mitigating effect of dietary fat.…”
Section: Discussionsupporting
confidence: 87%
“…The net effect would be increased methane production (Alstrup et al, 2015). In this context, studies by Moate et al (2017) and Bayat et al (2017), which reported lower MY than those observed in this study, used cows in peak lactation (71 and 89 DIM, respectively) compared with our study that used cows in late lactation (207 DIM).…”
Section: Discussioncontrasting
confidence: 58%
“…In their comprehensive review, Grainger and Beauchemin (2011) suggested that the mitigation potential of fats is 1 g CH 4 /kg DM intake for each 10 g fat/kg DM in the ration and this has shown persistent results, although no effect of the chain length of the fatty acids on the magnitude of mitigation has been detected. Feeding sunflower oil can effectively reduce enteric methane emissions of dairy cows (Bayat et al, 2017). Similar effects of vegetable oils on reducing methane emissions have been reported under in vitro conditions (Vargas et al, 2020).…”
Section: Enteric Methane Production By Cattle Fed Tropical Grassessupporting
confidence: 63%